THE EXTERNAL BIAS-DEPENDENT ELECTRIC FIELD AT HOLE-INJECTING ELECTRODE/α-NPD JUNCTION AND ITS RELATIONSHIP TO GAUSSIAN DISORDERED INTERFACE STATES - Bruno Cvikl (Journal of Energy Technology, 2024)
An alternative interpretation of two different sets of published temperature-dependent current-voltage α-NPD (i.e. N,N´-Di(1-naphthyl)-N,N´-diphenyl-(1,1´-biphenyl)-4,4´-diamine) organic semicon- ductor data is presented. The measurements are described in terms of the hole drift current density expressed with two parameters: the electric field at the hole-injecting interface, Eint, and, max, the hole mobility determined by the measured current density at the maximum value of the externally applied electric field, Ea, in a given experiment. The former parameter, depending on the contact résistance, may be a function of Ea but the latter is Ea independent, The fixed value of Eint signi- fies the occurrence of the space charge limited current, SCLC, within the electrode/α-NPD structures and the contact is ohmic. Then, the calculated weak bias‐dependent hole drift mobility, a function of Eint, equals the well‐known exponential bias‐dependent mobility, and saturates. The data not displaying SCLC characteristics are used for the calculation of Eint dependence on the applied field, Ea. It is shown that the quasi‐ohmic contacts cause Eint to become a strong double‐valued function of the externally applied electric field, Ea, described in terms of the distorted, inverted, high order parabola. The corresponding bias‐dependent hole drift mobility is non‐exponential and evolves on a considerably lower level than in SCLC cases. It is found that a sufficiently increased Ea alters the quasi‐ohmic contact/‐NPD region into the ohmic one. A simple model of a thin, net hole charged, electrode/‐NPD interface enables the relationship between the deduced interfacial electric field, Eint, and the Ea dependent Gaussian width, , as well as the energy shift of its peak, , along the negative binding energy is to be investigated. The current‐voltage method appears to be a helpful expedient for the investigation of the electric field at hole‐injecting electrode/organic interfaces.